PENGARUH MEDIA FLASHCARD TEMA MAKANAN TRADISIONAL PAGAR ALAM TERHADAP KEMAMPUAN MENGENAL ANGKA ANAK USIA 4-5 TAHUN DI PAUD KARTINI LAHAT - Saputri, Tamara; Akmillah Ilhami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using flashcard media with the theme of traditional Pagaralam food on the number recognition ability of children aged 4–5 years at PAUD Kartini Lahat. This study used a quantitative approach with a pre-experimental method with a one-group pre-test–post-test design. The research sample consisted of 16 children selected using a purposive sampling technique. Data collection techniques were carried out through observation, testing, and documentation. Data analysis was carried out using a normality test and continued with hypothesis testing. The average number recognition ability of children aged 4–5 years increased from 55.56 (pretest) to 91 (posttest), with a difference of 35.44 points. The Shapiro–Wilk normality test showed that the data were normally distributed (pretest Sig. 0.630; posttest Sig. 0.221). The results of the paired sample t-test showed a Sig.(2-tailed)value ofp < 0.001 < 0.05 witht = -73.404. Thefindings of this study indicate that the Pagar Alam traditional food theme flashcard media has a significant effect on the ability to recognize numbers in children aged 4-5 years, the Pagar Alam traditional food theme flashcard media is effective because it presents concrete, visual, and interactive learning. This media supports cognitive development, especially the ability to recognize numbers, as well as developing aspectsoflanguage,social-emotional, and physical motor skills. In addition,the use of flashcards also fosters children's understanding and love of local culture through the introduction of regional traditional foods.